A Meta-analysis of the relation between chemokine receptor 5 delta32 polymorphism and multiple sclerosis susceptibility. (May 2014) - Song, Gwan Gyu; Lee, Young Ho
Abstract : Objective : The aim of this study was to determine whether the functional chemokine receptor 5 delta32 (CCR5-Δ32) polymorphism is associated with multiple sclerosis (MS) susceptibility. Methods : Meta-analysis was conducted to determine the association between the CCR5-Δ32 polymorphism and overall incidence of MS as well frequency of relapsing-remitting (RR), primary progressive (PP), and secondary progressive (SP) MS subtypes. Results : In total, 3869 subjects from eight studies (MS 1666, controls 2203) were considered for meta-analysis. Meta-analysis showed no association between MS and the CCR5-Δ32 allele polymorphism (OR = 1.102, 95% CI = 0.830–1.462, p  = 0.502) with a mean frequency of 11.3% in MS patients and 10.4% in controls. Stratification by ethnicity indicated no association between the CCR5-Δ32 allele and MS in Europeans (OR = 0.958, 95% CI = 0.811–1.132, p  = 0.618). Meta-analysis by the disease subtype showed no association between RR-MS and the CCR5-Δ32 allele (OR = 1.234, 95% CI = 0.908–1.677, p  = 0.178). In addition, no association was found between the CCR5-Δ32 polymorphism and PP or SP-MS. Conclusions : Meta-analysis of 3869 subjects indicates a lack of association between the CCR5-Δ32 polymorphism and MS risk in Europeans.